ENVIRONMENTAL SUSTAINABILITY IN SMES: A STUDY OF EMERGING PATTERNS AND SECTORAL TRENDS - Muhammad Fahmi Latief; Ican Feriano Arindra (Resilience of Small Medium Business, 2025)
Objective: This research explores the integration of environmental orientation in SMEs' innovation strategies and its impact on sustainable organizational innovation (SOI) and business competitiveness, by highlighting the drivers, barriers and strategic alignment of environmental sustainability in the innovation process. Research Design & Methods: companies that align environmental strategy with long-term business objectives are more likely to develop dynamic capabilities that strengthen adaptability to market and environmental changes. The reporting process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, while methodological quality assessment was conducted using CASP (Critical Appraisal Skills Program) criteria. From a total of 67 articles that passed the initial quality assessment, 42 articles that met all relevance and data completeness criteria were further analyzed thematically. Findings: The findings show that the success of SOI in MSMEs depends on the integration of environmental issues into core business strategies. MSMEs adopt an environmental orientation through internal and external factors, and exhibit four main patterns: environmental responsiveness, learning-based adaptation, navigation of resource constraints, and alignment of strategies with sustainability goals. These aligned strategies drive long-term performance improvement and innovation. Implications & Recommendations: This study advises MSMEs to proactively integrate sustainability in innovation and business strategy. Policymakers need to support through training, incentives and green innovation support. Future research should focus on sectoral strategies and the role of digital transformation in sustainable innovation. Contribution & Value Added: This research broadens the horizon of sustainable entrepreneurship by demonstrating the strategic role of environmental orientation in driving MSME innovation, as well as providing guidance for businesses and policy makers in building a green business ecosystem.